Sistem Informasi Penggajian dengan Pencatatan Presensi Menggunakan Fingerprint Pada MTS Nu Jogoloyo Berbasis Multiuser - Arsito Ari Kuncoro; Muhamad Zaenudin (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Current technology has developed rapidly, computers are one of them. Almost all types of jobs require a computer to complete the task. In the field of computer education it is also very helpful, especially in terms of payroll services for teachers and employees who work as educators. MTs NU Jogoloyo Wonosalam Demak as an institution that has a large number of teachers and employees, besides that every day attendance officers are absent which results in difficulties in making payroll reports, especially recording and reporting still using manual methods so it takes longer time to record and deliver. report. In addition, sometimes there is a misunderstanding between attendance officers and teachers and employees regarding remuneration at the end of the month. In solving this payroll problem, the writer uses the Research and Development (R & D) method, while making applications can use high-level programming languages ​​such as Microsoft Visual Basic Ver 6.0. and SQL Server 2000 for data base management. Payroll applications are needed to simplify transactions and reporting on a monthly basis. With the use of this new payroll system software, it is hoped that it can produce quality information, improve service to employees and can assist in the decision-making process